PENEGAKAN HUKUM TERHADAP PEKERJA RUMAH TANGGA KORBAN KEKERASAN DALAM RUMAH TANGGA BERDASAR- KAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA DI KEPOLISIAN RESOR KOTA PEKANBARU - Niki Ardianti; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Violence in the home (domestic violence) is any act against someone, especially women, misery or suffering physical, sexual, psychological, and / or negligence of household including threat to commit acts, coercion, or deprivation of liberty unlawfully in scope household. The scope of household in Act No. 23 of 2004 on the Elimination of Domestic Violence include: a. Husband, wife, and children; b. People who have a family relationship with the person referred to in paragraph a by blood, marriage, dairy, care, and guardianship, were living in the household; and / or; c. People who are working to assist the household and living in the household. The problem of domestic violence from the beginning until now become a very interesting topic to be discussed in the problems kehidupaan household. Domestic violence against domestic workers occurred in Pekanbaru City Police has increased every year. This was due to several factors that influence so that the law enforcement process in Pekanbaru City Police is still not effective.The purpose of this thesis, namely: First, to determine enforcement against domestic workers as victims of crime in domestic violence in Pekanbaru City Police. Second, to determine the factors causing the lack of law enforcement in criminal domestic violence against domestic workers. This type of research can be classified in this type of sociological research. The research location is Pekanbaru City Police. Source data used are primary data and secondary data. Data collection techniques are interviews, and review of the literature. After the collected data was then analyzed qualitatively using the deductive method of drawing conclusions from things that are common to the things that are special.From the research, there are four factors that influence the process of law enforcement in Pekanbaru City Police. The first factor PKDRT Law enforcement still do not support the crime of domestic violence itself, because almost all domestic violence is considered as a complaint-based offense. Second, the lack of perception of the police in establishing the acts that qualify as felonies or misdemeanors. Third, do not support the means and facilities namely the lack of quality and quantity of personnel Unit PPA City Police Pekanbaru, poor room conditions Unit PPA terms of size, as well as the lack of the budget of the State in the implementation of a post mortem on the victim to support optimal law enforcement in Police Pekanbaru. Fourth, domestic workers are reluctant to give testimony related to the crime of domestic violence that is in nature.Keywords: Enforcement - Law - PRT - Victims - Domestic Violence